Re-examination of the contribution of substrates to energy expenditure during high-intensity intermittent exercise in endurance athletes - Aslankeser, Z.; Balci, S. S. (PeerJ, 2017)
Background: It has been believed that the contribution of fat oxidation to total energy expenditure is becoming negligible at higher exercise intensities (about 85% VO2max). The aim of the present study was to examine the changes in substrate oxidation during high-intensity interval exercise in young adult men. Methods: A total of 18 healthy well-trained (aged 19.60 ± 0.54 years, BMI = 22.19 ± 0.64 kg/m2, n = 10) and untrained (aged 20.25 ± 0.41 years, BMI = 22.78 ± 0.38 kg/m2, n = 8) young men volunteered to participate in this study. After an overnight fast, subjects were tested on a cycle ergometer and completed six 4-min bouts of cycling (at ~80% VO2max) with 2 min of rests between intervals. Energy expenditure and the substrate oxidation rate were measured during the experiment by using indirect calorimetry. The blood lactate concentration was collected immediately after each interval workout. Results: The fat oxidation rate during each workout was significantly different between the untrained and the athlete groups (p < 0.05), and the carbohydrate (CHO) oxidation rate during the experiment was similar between groups (p > 0.05). Moreover, lactate concentration significantly increased in the untrained group (p < 0.05), whereas it did not significantly change in the athlete group during the workouts (p > 0.05). Fat contribution to energy expenditure was significantly higher in the athlete group (~25%) than in the untrained group (~2%). Conclusions: The present study indicates that 17 times more fat oxidation was measured in the athlete group compared to the untrained group. However, the athletes had the same CHO oxidation rate as the recreationally active subjects during high-intensity intermittent exercise. Higher fat oxidation rate despite the same CHO oxidation rate may be related to higher performance in the trained group.